Mathematical Analysis of Robust Anisotropic Diffusion Filter for Ultrasound Images - Kushwaha, Sumit (International Journal of Computer Sciences and Engineering, 2025)
Anisotropic Diffusion is very efficient non-linear image processing PDE based technique which simultaneously restore images and enhance image features for 2-D or, 3-D images. This technique is described by local eigenvalues and local eigenvectors of the anisotropic diffusion tensor field where anisotropic diffusion coefficients are depending on direction and position. Here, mathematical analysis of robust anisotropic diffusion (RAD) filter for ultrasound (US) image has been discussed in this paper. It includes probabilistic memory mechanism and speckle statistics models of tissues characterization and adapts the anisotropic diffusion tensor to the ultrasound image iteratively. Higher frequency absorbed by tissue and skin but cannot penetrate deeply in comparison to lower frequency which give poorer image quality by echo signals, so we get an inferior quality image with some clinical information loss. This clinical information loss is restored by iterative process of various state-of-the-art filters, but discussed RAD filter shows better performance in terms of measured MSE and SSIM index, with including memory mechanism and speckle statistics, and preserves the relevant tissue details for clinical purposes.